2012
DOI: 10.3390/toxins5010016
|View full text |Cite
|
Sign up to set email alerts
|

Onabotulinumtoxin A for Treating Overactive/Poor Compliant Bladders in Children and Adolescents with Neurogenic Bladder Secondary to Myelomeningocele

Abstract: This retrospective study was performed to verify the efficacy and safety of Onabotulinumtoxin A (BTX-A) in treating children with neurogenic bladder (NB) secondary to myelomeningocele (MMC) with detrusor overactivity/low compliance. From January 2002 to June 2011, 47 patients out of 68 with neuropathic bladder were selected (22 females, 25 males, age range 5–17 years; mean age 10.7 years at first injection). They presented overactive/poor compliant neurogenic bladders on clean intermittent catheterization, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
(22 reference statements)
0
24
0
Order By: Relevance
“…There were no perioperative urinary tract infections in six studies . Three studies reported post‐injections urinary tract infections, rates ranging from 4% to 29% . No other significant complications were noted, especially no muscular weakness or fatigue.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…There were no perioperative urinary tract infections in six studies . Three studies reported post‐injections urinary tract infections, rates ranging from 4% to 29% . No other significant complications were noted, especially no muscular weakness or fatigue.…”
Section: Resultsmentioning
confidence: 92%
“…Following evaluation of the full text of the remaining 15 papers, three more studies were excluded as they were overlapping series. The remaining 12 articles, published between 2002 and 2015, were included in this systematic review (n = 261 patients) and fully analyzed …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of clean intermittent catheterization and anticholinergics [3], urethral dilation [4] and overnight catheter drainage [5] - and recently the use of onabotulinumtoxinA [6,7,8,9] - have all been introduced to optimize bladder storage and/or bladder emptying. The identification of an infant with detrusor sphincter dyssynergy is critical, since the developing bladder and kidneys are most vulnerable during the first several years of life.…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum toxin A (Botox ® , Allergan, Irvine, Calif.) is recommended as the second-line treatment for those patients who have an inadequate response to or are intolerant to anticholinergic medication [4,5]. In the past ten years, intradetrusor injection of BTX-A was performed while avoiding the trigone to prevent VUR.…”
Section: Introductionmentioning
confidence: 99%